U.S. Deaf Community Perspectives on Automatic Sign Language Translation - Tran, Nina; Ladner, Richard; Bragg, Danielle (ACM SIGACCESS Conference on Computers and Accessibility, 2023)
Millions of Deaf and hard-of-hearing (DHH) people primarily use a sign language for communication, but there is a lack of adequate sign language interpreting to fill these communication needs. Development of automatic sign language translation (ASLT) systems could help translate between a sign language and spoken language in situations where human interpreters are unavailable, and recent advances in large multi-lingual language models may soon enable ASLT to become a reality. Despite the potential for ASLT, Deaf community perspectives on and requirements for such technologies are poorly understood. In this work, we conduct a survey of Deaf community perspectives in the U.S. on ASLT in order to inform the development of ASLT systems that meet user needs and minimize harms. Our results shed light on scenarios where DHH users in the U.S. might want to use ASLT, their performance expectations for ASLT in these scenarios, design preferences for ASLT interfaces,